TEMPERATURE- AND PH-DEPENDENCE OF ALBITE DISSOLUTION RATE AT ACID PH - Chen Y.; Brantley S.L. (My University, 1997)
Albite dissolution experiments performed in solutions at pH below neutral at 5°, 50° and 90°C combined with results from the literature for albite dissolution at other temperatures show that the pH- and temperature-dependence of dissolution can be modeled using the following equation for highly unsaturated (far-from-equilibrium) conditions: logr = -2.71 -3410/T -0.5pH where r is the dissolution rate in mol albite cm-2 s-1; and T is temperature in K. The above equation is valid between pH 1 and 5 and temperatures from 5° to 300°C. The activation energy of dissolution for albite for this temperature and pH range is 15.6 +/- 0.8 kcal mol-1.However, in addition to pH, other species in solution also affect the feldspar dissolution rate: these variations may be modeled as a ΔG-effect or an ion-specific adsorption effect. Because our measurements were all completed for values of #ΔG# < 11 kcal mol-1, where the affinity effect should be small (assuming a linear model), we used an ion inhibition model to describe our data. Assuming feldspar dissolution is controlled by competitive adsorption of hydrogen and aluminum on the feldspar surface, we use a Langmuir competitive adsorption model to fit the data:r = k'[KH{H+}/(1 + KH{H+} +KAl {Al3+})]12 where k' is the apparent rate constant (mol cm-2 s-1); KH is the proton adsorption equilibrium constant; KAl is the Al adsorption equilibrium constant; and {H+} and {Al3+} are activities of H+ and Al3+ in solution, respectively. The temperature-dependent parameters (k', KH, KAl) are modeled using the Arrhenius and van't Hoff equations. The values of ΔH are assumed equal to 8 and -8 kcal mol-1 for Al3+ and H+, respectively. A value of 10-0.97 is used for KH at 25°C. The values of k' and KAl at 25°C have been determined by non-linear curve fitting to be 1.7 x 10-14 mol cm-2 s-1 and 2.0 x 103, respectively.The adsorption model fits the experimental data more closely than the simpler rate model, indicating that the model is consistent with the observed pH-, Al- and temperature-dependence of feldspar dissolution between 5° and 300°C. More data are needed to evaluate competitive effects of Na+ or other ions, or the effect of ΔG for near-equilibrium solutions. This model emphasizes that the effect of inhibition by adsorbed cations should be greater at higher temperature (< 50°C), due to the positive value of the adsorption enthalpy of cation adsorption on oxide surfaces.
Keywords: ACTIVATION ENERGY; ALBITE; DISSOLUTION; RATES